Crystal structure of dimethyl 5-(dibenzylamino)isophthalate, C24H23NO4 - Li Yaping; Sun Dajun; Ming Julia; Su Guanfang (Zeitschrift für Kristallographie - New Crystal Structures, 2016)
C24H23NO4, monoclinic, P21/n (no. 14), a = 13.492(6) Å, b = 9.259(4) Å, c = 15.993(8) Å, β = 94.009(9)°, V = 1993.0(16) Å3, Z = 4, Rgt(F) = 0.0409, wRref(F2) = 0.1201, T = 293(2) K.